2020
DOI: 10.3389/fendo.2020.00169
|View full text |Cite
|
Sign up to set email alerts
|

The miRNA-29b Is Downregulated in Placenta During Gestational Diabetes Mellitus and May Alter Placenta Development by Regulating Trophoblast Migration and Invasion Through a HIF3A-Dependent Mechanism

Abstract: Gestational diabetes mellitus (GDM) is a disease that changes the function of microvascular of placenta. MicroRNA (miRNA) expression in placenta may contribute to the pathogenesis of GDM. Here, we evaluate the role and function of miR-29b in the development of GDM. This study discovered that miR-29b expression was lower in placentas derived from patients with GDM than that in control placentas. MiR-29b over-expression inhibited cell growth and migration, and miR-29b knockdown promoted cell migration. Then we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…The placenta expresses more than 500 miRNA species [22,23] attributable in part by two placenta expressed miRNA clusters; the chromosome 19 and 14 miRNA clusters; C19MC and C14MC, respectively. Dysregulated placenta-associated miRNAs [24][25][26][27] as well as altered circulating miRNA profiles [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] have been associated with GDM, mirroring physiological and pathological changes during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The placenta expresses more than 500 miRNA species [22,23] attributable in part by two placenta expressed miRNA clusters; the chromosome 19 and 14 miRNA clusters; C19MC and C14MC, respectively. Dysregulated placenta-associated miRNAs [24][25][26][27] as well as altered circulating miRNA profiles [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] have been associated with GDM, mirroring physiological and pathological changes during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-21 was down-regulated in the sera and placentas of GDM patients compared to healthy pregnant women, and thus inhibited cell growth and infiltration by up-regulating PPAR-α ( 83 ). In addition, miR-29b expression was lower in placentas derived from patients with GDM than those in the control group ( 84 ). At a molecular level, hypoxia-inducible factor 3 alpha (HIF3A) was found to be a direct target of miR-29b, with two specific binding sites at the recognition sequences of miR-29b in the 3’-UTR of HIF3A mRNA, which, in turn, was negatively correlated with the miR-29b expression level ( 84 ).…”
Section: Role Of Non-coding Rnas and Evs In Gdmmentioning
confidence: 88%
“…In addition, miR-29b expression was lower in placentas derived from patients with GDM than those in the control group ( 84 ). At a molecular level, hypoxia-inducible factor 3 alpha (HIF3A) was found to be a direct target of miR-29b, with two specific binding sites at the recognition sequences of miR-29b in the 3’-UTR of HIF3A mRNA, which, in turn, was negatively correlated with the miR-29b expression level ( 84 ). The other study regarding miR-29b drew a similar conclusion, suggesting that the effect of miR-29b was related to the PI3K/Akt signaling pathway at a molecular level ( 85 ).…”
Section: Role Of Non-coding Rnas and Evs In Gdmmentioning
confidence: 88%
“…Sun et al [26] observed that the placental expression levels of miR-29b were lower in a GDM group compared to controls. Moreover, by using the trophoblast cell line HTR8/SVneo with an miR-29b mimetic or inhibitor, the authors observed that miR-29b over-expression inhibited cell growth, late apoptosis, migration and invasion; and miR-29b knockdown promoted cell migration and invasion.…”
Section: Mirnasmentioning
confidence: 99%